FISHER WOMEN IN KERALA FIGHT BACK : A Preliminary Study on the activities and struggles spearheaded by Theeradesa Mahila Vedi, the women's wing of Kerala Swathanthra Matsya Thozhilali Federation - OAMJIE JOHN
This is only a preliminary documentation of the activities and agitations of Theeradesa Mahila Vedi since its inception. The geographical focus of the study is coastal south Kerala. The study is an attempt to document the issues and vulnerabilities that are addressed by fisherwomen in the context of globalization. It also looks in to the impact of globalization and the new development initiatives on the livelihood conditions of fisherwomen. It is a historical documentation of the movement of issues like various forms of denial of rights and the impact of market on the fish workers community. Issues like gender bias, violence and sexual harassment on fisherwomen and their girl children are also briefly covered. A comprehensive study will be followed covering the entire Kerala coast and other gender related issues